1989
DOI: 10.1080/10407788908944678
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Mixed Convection in the Entrance Region of a Horizontal Annulus

Abstract: A numerical study is presented for the combined forced and free convection in the entrance region of a horiwnlnl annulus with mdius m ' o of 2. Results are presented for developing velocity pmfiles, temperature Jield, local pressure gmdient, and the circumferentially avemged Nusself number. These resulfs reveal thal the buoy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…This investigation revealed that the Nusselt number is considerably greater for developing flow than the corresponding values for fully developed flow over a significant portion of the annulus. Karki and Patankar [2] presented a numerical study for the combined convection in the entrance region of a horizontal annulus with a fixed radius ratio of 2. The results were presented for developing velocity and temperature fields, local pressure gradient, and the circumferentially averaged Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation revealed that the Nusselt number is considerably greater for developing flow than the corresponding values for fully developed flow over a significant portion of the annulus. Karki and Patankar [2] presented a numerical study for the combined convection in the entrance region of a horizontal annulus with a fixed radius ratio of 2. The results were presented for developing velocity and temperature fields, local pressure gradient, and the circumferentially averaged Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…He observed that flow and thermal behavior depended on heat fluxes imposed on the inner cylinder within the isothermal enclosure. Karki and Patankar [7] presented a numerical study for the combined convection in the entrance region of a horizontal annulus with a fixed radius ratio of 2. The results were presented for developing velocity and temperature fields, local pressure gradient, and the circumferentially averaged Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…The condensers for seawater distillation, underground electric transmission cable using pressurized gas, cooling of turbine rotors, the chemical vapor deposition processes for the fabrication of semiconductor devices, the thermal storage systems, the food processes, and the thermal insulation are additional examples where the results of buoyancy-influenced convection heat transfer in annulus pipe are useful. Investigations [7][8][9][10][11][12] on mixed convection in horizontal annuli revealed that heat transfer augmentation for simultaneously developing flow is higher than that for fully developed flow [13][14][15][16][17][18]. It has been observed that further improvement in heat transfer performance can be achieved by using nanofluid [19,20] in place of conventional cooling fluids such as water, oil, and air.…”
Section: Introductionmentioning
confidence: 99%